Pembingkaian Media Terhadap Kasus Donasi Agus Salim di VIVA.co.id dalam Perspektif Inklusi Sosial - Baiq Nisrina Lydya; Pribadi, Farid (Paradigma, 2026)
This study aims to analyze media framing of the Agus Salim donation controversy on VIVA.co.id from a social inclusion perspective. The controversy began with an acid attack against Agus Salim that triggered public solidarity through a donation campaign, but later developed into a dispute over transparency and the management of donation funds. This research employs a qualitative approach using purposive sampling by selecting three news articles representing three phases of coverage: the incident phase, the donation conflict phase, and the intervention phase by the Ministry of Social Affairs. The analysis applies Robert N. Entman’s framing model, which includes define problems, diagnose causes, make moral judgment, and treatment recommendation. The findings indicate a shift in framing from neutral coverage in the initial phase to sensational and increasingly exclusionary framing during the conflict and resolution phases. In the early phase, Agus Salim was positioned as a victim, while in subsequent phases he was more frequently portrayed as a conflict actor, thereby reducing his representation as a person with disabilities who possesses rights and agency. Framing that emphasizes personal conflict and netizen reactions has the potential to reinforce stigma and weaken the principles of social inclusion. This study concludes that VIVA.co.id’s coverage has not fully supported social inclusion, as it tends to prioritize sensational aspects over the affirmation of rights, dignity, and equality of persons with disabilities.